On Topological Indices of mth Chain Hex-Derived Network of Third Type - Huo, Yuhong; Ali, Haidar; Binyamin, Muhammad Ahsan; Asghar, Syed Sheraz; Babar, Usman; Liu, Jia-Bao (Frontiers in Physics, 2020)
In theoretical chemistry, the numerical parameters that are used to characterize the molecular topology of graphs are called topological indices. Several physical and chemical properties like boiling point, entropy, heat formation, and vaporization enthalpy of chemical compounds can be determined through these topological indices. Graph theory has a considerable use in evaluating the relation of various topological indices of some derived graphs. In this article, we will compute the topological indices like Randić, first Zagreb, harmonic, augmented Zagreb, atom-bond connectivity, and geometric-arithmetic indices for chain hex-derived network of type 3 CHDN3(m,n) for different cases of m and n. We will also compute the numerical computation and graphical view to justify our results. Mathematics Subject Classification: 05C12, 05C90